Exome Sequencing Identifies TENM4 as a Novel Candidate Gene for Schizophrenia in the SCZD2 Locus at 11q14-21 - Xue, Chao-Biao; Xu, Zhou-Heng; Zhu, Jun; Wu, Yu; Zhuang, Xi-Hang; Chen, Qu-Liang; Wu, Cai-Ru; Hu, Jin-Tao; Zhou, Hou-Shi; Xie, Wei-Hang; Yi, Xin; Yu, Shan-Shan; et al. (Frontiers in Genetics, 2019)
Schizophrenia is a complex psychiatric disorder with high genetic heterogeneity, however, the contribution of rare mutations to the disease etiology remains to be further elucidated. We herein performed exome sequencing in a Han Chinese schizophrenia family and identified a missense mutation (c.6724C>T, p.R2242C) in the teneurin transmembrane protein 4 (TENM4) gene in the SCZD2 locus, a region previously linked to schizophrenia at 11q14-21. The mutation was confirmed to co-segregate with the schizophrenia phenotype in the family. Subsequent investigation of TENM4 exons 31, 32 and 33 adjacent to the p.R2242C mutation revealed two additional missense mutations in 120 sporadic schizophrenic patients. Residues mutated in these mutations, which are predicted to be deleterious to protein function, were highly conserved among vertebrates. These mutations were not detected in 1000 Genomes, NHLBI Exome Sequencing Project databases or our in-house 1136 non-schizophrenic control exomes. Analysis of RNA-Seq data showed that TENM4 is expressed in the brain with high abundance and specificity. In line with the important role of TENM4 in central nervous system development, our findings suggested increased rare variants in TENM4 could be associated with schizophrenia, and thus TENM4 could be a novel candidate gene for schizophrenia in the SCZD2 locus.